Chemosensors principles, strategies, and applications - Wang, Binghe; Anslyn, Eric V., 1960- (Wiley series in drug discovery and development ;, 2011)
"This book offers a general overview of chemosensors and their applications, including topics like molecular recognition, detection methods, design strategies, and important biological issues"--